Investigating the origin of chloroform in soils and groundwater using carbon and chlorine stable isotopes analysis - Breider, Florian (My University, 2013)
Chloroform (CHCl3) has been considered for a long time as an anthropogenic contaminant which is known to be possibly carcinogenic to humans. Chloroform is also an important contributor to gaseous chlorine in the atmosphere and may catalyze some chemical reactions in the lower atmosphere. The presence of chloroform in aquatic and terrestrial environments has been widely demonstrated. The frequent detection of chloroform in forest soils, peatland and groundwater in absence of other anthropogenic contaminants suggests that chloroform may be produced naturally by biogeochemical processes. Numerous studies on natural organohalogens have suggested that enzymes such as haloperoxidases (e.g. chloroperoxidase from Caldariomyces fumago) and halogenases excreted by some fungi, plants and bacteria could play an important role in biosynthesis of chlorinated organic compounds in soils. Although the natural formation of chloroform in some forest soils and peatlands is rather well establish, it is difficult to demonstrate a natural origin of chloroform in groundwater as chloroform is widely used as solvent or chemical reagent and can be transported over extended distances from anthropogenic sources. For risk assessment and to implement appropriate remediation measures, there is a need for methods to differentiate between natural and anthropogenic chloroform. Moreover, little is known about the mechanisms leading to the formation of natural chloroform in the terrestrial environment.
This PhD thesis investigates if stable isotope methods can be used to distinguish between different sources of chloroform and provide additional insight into the mechanism of natural chloroform formation. It is expected that anthropogenic and natural chloroform have a different isotope signature due to the differences in the origin of the carbon and formation mechanisms. To evaluate the feasibility of the method, the isotope signature of chloroform was characterized at forested sites where chloroform is likely produced naturally and compared to the isotope signature in underlying groundwater. In addition, the isotope composition of industrial chloroform and chloroform at sites with known anthropogenic contamination was evaluated. Based on previous studies, chloroform formation might proceed via the formation of trichloroacetyl-containing compounds (TCAc) from which chloroform is released by hydrolysis. To confirm this hypothesis, the concentration and isotope ratio of TCAc was quantified as well at the sites where natural chloroform production was observed. The mechanism of chloroform formation and factors that control the isotope ratio of chloroform were investigated in more detailed using laboratory chlorination experiments. In addition to NOM, simple model compounds were used which make it easier to relate observed isotope trends to underlying reaction mechanisms. Chlorination was induced by using chloroperoxidase (CPO) and HOCl, which is expected to be the active compound also during enzymatic chlorination. A first set of studies explored the role of TCAc in chloroform formation in more detail. In these studies, the isotope composition of chloroform and TCAc containing compounds from laboratory incubation studies were compared to field observations and to predictions from an analytical model. In order to evaluate the contribution of different functional groups to chloroform formation, isotope effects associated with chlorination of model compounds with specific function groupds were compared with isotope effects during chlorination of NOM. Finally a series of experiments were carried out that focues on chlorine isotope analysis to explore potential rate-limiting steps in chlorination in more detailed. These experiments also provided insight into the potential chlorine isotope composition of naturally formed chloroform.
In order to demonstrate that carbon isotope analysis can be used to determine the origin of chloroform in groundwater, the δ13C of chloroform was determined in soil gas and groundwater at five different sites including three forested areas, one urban site and one landfill. The δ13C of chloroform at the water table (-22.0‰) of forest sites corresponded well to the δ13C of soil gas chloroform (-22.8 and -26.2‰) demonstrating that chloroform maintains its characteristic isotope signature during transport through the unsaturated zone. At the three forested sites, the δ13C of groundwater δ13C from -22‰ to -27 ‰) was close to the values of soil gas chloroform indicating a natural origin of chloroform. This conclusion is plausible as the three sampling sites were located within spruce and pine forest which are associated with soils that are favorable for chloroform production. In contrast, chloroform from the landfill (-42.1‰) and urban (-47.0‰) sampling sites have clearly an anthropogenic signature (δ13C from -43‰ to -63‰) consistent with a concentration higher than at the three forested sites. Chloroform was detected in groundwater samples as old as 35 years demonstrating that chloroform can persist over extended periods in oxic groundwater. The isotope analysis of groundwater samples collected in spruce forest indicates that the origin of chloroform can still be determined based on isotope composition even if chloroform was transported over an extensive distance. The δ13C of chloroform sampled down gradient of a spruce plantation with an average groundwater age of 30 years had a δ13C of -24‰, which is still within the range of the 13C in soil gas. Thus, the strong difference in δ13C between natural and industrial chloroform makes it possible to unmistakably identify the origin of chloroform even if the some changes of the isotope composition occur during transport.
The TCAc in some forest soils are strongly enriched in 13C (-10‰) compared to natural chloroform. Chlorination experiments combined with a mathematical model have revealed that TCAc could play a fundamental role in the formation of chloroform. Indeed, the laboratory experiments have shown that in addition to chloroform 13C-enriched TCAc are also formed during the chlorination of NOM and humic substances. The large isotope fractionations measured experimentally (kinetic isotope effect from 1.014 to 1.018) for the hydrolysis of TCAc were comparable with those observed for field samples and for the hydrolysis of trichloropropanone. The kinetic isotope effect (KIE) corresponds to the difference in reactions due to the presence of a heavy carbon isotope at the position where hydrolysis takes place. The strong enrichment of TCAc in 13C indicates that a fraction of the trichloromethyl groups is released as chloroform by hydrolysis. Using a mathematical model combined with the fractionation factors determined experimentally, it was shown that when the formation of TCAc and hydrolysis reach a steady state, the isotope composition of chloroform is expected to correspond to isotope ratio of NOM while TCAc should be enriched in 13C. This study confirms that TCAc are reaction intermediates which subsequently release chloroform by hydrolysis, and explains why natural chloroform has a similar isotope signature as NOM despite a large carbon isotope fractionation during its release.
In order to assess the role of selected NOM functional groups in the chloroform formation process as function of pH, the isotopic trends of chloroform produced at different pH (4, 7 and 8) by chemical chlorination of model compounds, humic acid and SOM were measured. As phenolic and ketone functional groups are among the most abundant reactive NOM moieties, phenol and 2-propanone were chosen as model compounds. The isotopic trends of chloroform formed by chlorination of humic acid and NOM were compared with those measured for the formation of chloroform from model compounds to explore which functional groups in NOM might contribute to chloroform formation. These chlorination experiments have demonstrated that the apparent kinetic isotope effects for chloroform formation from model compounds representing NOM functional groups are strongly pH-dependent. Chloroform production from phenol displays a normal KIE (KIE>1), at pH 4 and 7, whereas at pH 8 the process gives rise to an inverse KIE (KIE<1). For chloroform production from 2-propanone, an opposite pH-dependence is observed with a normal KIE at higher pH (7 and 8) and an inverse KIE at lower pH (4). These results indicate that for both chloroform precursors the reaction mechanism and/or the rate limiting step in the sequence of reactions leading to chloroform changes as a function of pH. The comparison of KIE associated with the chlorination of model compounds and NOM suggest that phenolic and ketone groups might be responsible for chloroform formation upon chlorination of NOM in forest soils.
Chlorine isotopes analysis of chloroform sources might contribute to better discriminate natural and industrial chloroform in the terrestrial environment. To estimate the expected range of δ37Cl values for chloroform naturally formed in forest soils and to gain a better understanding of the mechanisms involved in the CPO-catalyzed chlorination of humic substances, abiotic and enzymatic chlorination experiments were carried out. The chlorine isotope analysis of chloroform formed by CPO-catalyzed chlorination at different pH suggested that the formation of an HOCl−ferriprotoporphyrin(IX) intermediate is likely rate-limiting in forest soils (KIE between 1.006 and 1.007). Therefore, in the case where natural chloroform would be produced in forest soils by microorganism excreting extracellular iron-containing CPO and with chloride from atmospheric deposition with δ37Cl value between -1‰ and 1‰, the δ37Cl value of natural chloroform should ranges between -5‰ and -8‰. Thus, natural and industrial chloroform sources might be distinguished from the chlorine isotope composition since the δ37Cl values of industrial chloroform range between 0.32 and -5.4‰ while natural chloroform is expected to be more depleted in 37Cl. The analysis of the KIEs associated with the abiotic and enzyme catalyzed chlorination suggests also that the enzymatic chlorination of NOM occurs via the formation of free hypochlorous acid. These results support the hypothesis according to the CPO-catalyzed chlorination occur via chemo-enzymatic pathway where transiently formed hypochlorous acid diffuse out of the enzyme and react with an organic substrate.
This thesis demonstrates that carbon and chlorine isotope analysis constitute a method of choice to determine the origin of chloroform in soils and groundwater and to study the formation mechanisms. However, the fate of chloroform and related compounds in the studied forest soils and groundwater remains unclear. The biodegradation of anthropogenic chloroform might produces δ13C values in the same range as natural chloroform, underscoring the need to evaluate the isotope signature at contaminated sites with care. Although compound-specific isotope analysis is a valuable approach for source fingerprinting, the δ13C values of chloroform must be interpreted within the detailed hydrogeological and geochemical context of the site. The isotope analysis has also provided valuable information about the role of TCAc in the chloroform formation mechanism and the reactivities of the some functional groups representative of NOM.
Thèse de doctorat : Université de Neuchâtel, 2013
Keywords: Chloroform; trichloroacetyl-containing compounds; trichloroacetic acid; chlorination; hydrolysis; compound-specific isotope analysis; stable isotope; kinetic isotope effect; chloroperoxidase; forest soils; groundwater